L’action située dans le développement de l’activité - Pascal Béguin; Yves Clot (Activités)
After briefly attempting to describe situated action and distributed cognition, we examine their contributions from the point of view of activity theories and more specifically based on the relations between the functioning and development of activity. We argue that situated action identifies a limit in cognitive psychology in seeking to bring the subject back into the situation and in reintegrating him/her socially. However, in situating the organization of action outside the subject, it is finally the characteristics of the situation that explain activity. This epistemological pendulum, already discussed by H. Wallon, does not allow an understanding of the development of activity, nor the relation between what is given in the work situation and what the actors create in the situation.